English for Physics Laboratory Work: Needs Analysis of Undergraduate Learners - Azahra, Khadijah; Aini, Latifa Marwaatul; Wahyunengsih (Impulse: Journal of Research and Innovation in Physics Education, 2025)
The increasing use of English in laboratory manuals requires Physics Education students to possess adequate language skills in order to carry out practical activities effectively. However, many students still struggle to understand scientific terminology and interpret instructions written in English. Previous studies have also shown a gap between the linguistic demands of laboratory work and students’ actual language proficiency, making needs analysis essential to conduct. This study aims to identify the English language needs of Physics Education students and the linguistic challenges they encounter during laboratory practice. A descriptive survey method was employed through a mixed-method approach involving fifty students at UIN Syarif Hidayatullah Jakarta. Data were collected using an ESP-based questionnaire and semi-structured interviews, then analyzed through descriptive statistics and thematic analysis. The findings indicate that reading is the most needed skill (M = 4.1; 78%), followed by listening (M = 3.9; 75%), speaking (M = 3.8; 72%), and writing (M = 3.7; 70%). Limited mastery of scientific vocabulary emerged as the main obstacle in understanding texts and instructions. Practically, this study contributes by highlighting ESP needs that are specific to the physics laboratory context, which differ from those addressed in general ESP instruction. These findings emphasize the importance of ESP teaching that focuses on technical vocabulary development, comprehension of procedural texts, and listening practices relevant to real laboratory situations.